Addressing Femicide in Honduras through the Spotlight Initiative: A Study of the Implementation of the UN–EU Global Program - Hanif, M. Rayhan; Eriyanti, Linda Dwi; Prabhawati, Adhiningasih (Center of Gender Studies and Child of State Islamic Institute of Metro, 2025)
Honduras is one of the countries with the highest rates of femicide in Central America. The high rate of femicide in Honduras has prompted the United Nations and the European Union to assist Honduras in addressing the issue of femicide through the Spotlight Initiative program. This study also aims to examine the implementation of the Spotlight Initiative program in addressing femicide in Honduras from 2019 to 2023. This study is important to fill the gap in research on femicide in Latin America, particularly Honduras, and to analyze the Spotlight Initiative Program. This study uses a qualitative approach with descriptive analysis. This study uses literature review as data collection. The results of the study indicate that the implementation was carried out by the United Nations and the European Union by strengthening policies and legislation, strengthening institutions, preventing gender-based violence, strengthening gender-responsive services, strengthening data, and strengthening women's movements. The conclusion of the study shows that although the program's implementation is in line with liberal feminist theory, the implementation of the Spotlight Initiative in addressing femicide in Honduras has not met the indicators of gender mainstreaming. [Honduras adalah salah satu negara yang memiliki tingkat femisida tertinggi di kawasan Amerika Tengah. Tingginya angka femisida di Honduras mendorong PBB dan Uni Eropa membantu Honduras dalam menyelesaikan permasalahan femisida melalui program Spotlight Initiative. Penelitian ini juga bertujuan untuk mengetahui implementasi program Spotlight Initiative dalam menangani femisida di Honduras pada tahun 2019 hingga tahun 2023. Kajian ini penting dilakukan untuk mengisi kekosongan penelitian tentang femisida di Kawasan Amerika Latin, khususnya Honduras, dan analisis terhadap Program Spotlight Initiative. Penelitian ini menggunakan pendekatan kualitatif dengan analisis deskriptif. Penelitian ini menggunakan studi pustaka sebagai pengumpulan data. Hasil penelitian menyebutkan bahwa implementasi dilakukan oleh PBB dan Uni Eropa dengan memperkuat kebijakan dan perundang - undangan, memperkuat institusi, mencegah kekerasan berbasis gender, memperkuat layanan responsif gender, memperkuat data, dan memperkuat gerakan perempuan. Kesimpulan kajian menunjukkan meskipun pelaksanaan program sudah sesuai dengan teori feminisme liberal, tetapi Implementasi Spotlight Initiative dalam menangani femisida di Honduras belum memenuhi indikator di dalam pengarusutamaan gender (Gender Mainstreaming)].